Sejarah Pendidikan Indonesia Baru: Perkembangan Pembelajaran Sejarah Berbasis Artificial Intelligence (AI) 4.0 - Fatimah, Nurul; Octaviani, Dessy (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
The development of education in Indonesia in the 4.0 era is quite significant in terms of learning. The emergence of artificial intelligence (AI) technology provides opportunities and challenges for implementing history learning at the elementary to high school levels. This research aims to answer the problem of why AI technology is important in learning history and what its benefits are. The method used in research is the historical research method. The results of this research show that the development of history learning based on artificial intelligence (AI) in the digital era 4.0 continues to develop, making history learning a challenge for educators because it not only requires an understanding of historical facts but also interpretation and analysis as well as the application of learning strategies using AI. The benefits of using AI in history learning are increasing learning efficiency by reducing the time needed to search for information, increasing student interaction with learning material through the use of technology that attracts attention, and increasing students' understanding of the historical context through data visualization and analysis. The challenge in using AI is the teacher's lack of ability to follow developments in AI-based learning, and the use of AI technology in history learning is the lack of relevant and quality data. The challenge in using AI is the teacher's lack of ability to follow developments in AI-based learning, and the use of AI technology in history learning is the lack of relevant and quality data.